2005
DOI: 10.1148/radiol.2371041879
|View full text |Cite
|
Sign up to set email alerts
|

CT Images of Abdomen and Pelvis: Effect of Nonlinear Three-dimensional Optimized Reconstruction Algorithm on Image Quality and Lesion Characteristics

Abstract: The purpose of this study was to retrospectively assess the effect of a postprocessing nonlinear three-dimensional optimized reconstruction algorithm on image quality and lesion characteristics in abdominal and pelvic computed tomographic (CT) images. Institutional review board approved the HIPAA-compliant study protocol; informed consent was waived. Abdominal and pelvic CT images (40 patients; male-female ratio, 20:20; age range, 28-86 years) at 5-mm (n = 20) and 2-mm (n = 20) section thicknesses were postpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 8 publications
3
21
0
2
Order By: Relevance
“…The significant decrease in mean HU of the liver parenchyma from the early to late contrast phase was due to contrast washout. In general, our results are consistent with previously published phantom and patient studies, with non-linear 2D or 3D filters, on noise and radiation dose reduction for abdominal CT (5,7,8,14,16,19,20). For example, Rizzo et al Some recent CT radiation dose reduction studies using hybrid iterative reconstruction techniques have demonstrated up to 50-75% dose reduction for abdominal examinations (9).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The significant decrease in mean HU of the liver parenchyma from the early to late contrast phase was due to contrast washout. In general, our results are consistent with previously published phantom and patient studies, with non-linear 2D or 3D filters, on noise and radiation dose reduction for abdominal CT (5,7,8,14,16,19,20). For example, Rizzo et al Some recent CT radiation dose reduction studies using hybrid iterative reconstruction techniques have demonstrated up to 50-75% dose reduction for abdominal examinations (9).…”
Section: Discussionsupporting
confidence: 92%
“…The study is based on a sample size of only 12 patients. This small number was mainly due to the ethical considerations of exposing patients to additional radiation doses, and is to some extent compensated by using six observers, compared to one to three readers in most earlier studies (4,5,7,14,16,18,21,22). As described above, the chosen sample size was clearly adequate for obtaining significant results for most of the criteria evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the published clinical studies on noise reduction filters used reduced tube current to achieve images with less radiation dose (8,9,11). Despite the fact that both the reduction of tube current and tube potential cause a decrease in radiation dose, the reduction of tube potential has an important advantage: the increase in image contrast, which is more pronounced for materials with high effective atomic number, like iodine (4).…”
Section: Discussionmentioning
confidence: 99%
“…Es können lineare und nicht lineare Filter unterschieden werden, wobei sich letztere dadurch auszeichnen, dass in die Analyse eines Pixels auch die direkt benachbarten Pixel einbezogen werden. Untersuchungen mit verschiedenen nicht linearen Filtern in den letzten Jahren erbrachten ermutigende Ergebnisse [15,16] …”
Section: Interobserverreliabilitätunclassified